2006
DOI: 10.2320/matertrans.47.2898
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of Poly- and Single-Crystalline BaTi<SUB>2</SUB>O<SUB>5</SUB>

Abstract: Non-oriented and (010) oriented poly-crystalline BaTi 2 O 5 (BT 2 ) was prepared by hot-pressing and arc-melting, respectively. The dielectric properties of poly-crystalline BT 2 were compared with those of single-crystalline BT 2 prepared by a floating zone method. The maximum permittivity of (010) oriented poly-crystalline BT 2 was 2000 at 720 K, whereas that of single-crystalline BT 2 was 6000 at the Curie temperature, T c (750 K). The permittivity of non-oriented poly-crystalline BT 2 was 30 to 300, having… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 22 publications
0
21
2
Order By: Relevance
“…Recently, the dense and single-phased BT 2 sintered bodies with a preferred growth direction along the b-axis were obtained via a solid-state reaction of BaCo 3 with Tio 2 at 1025°C in air using B 2 o 3 as the additive [11]. The permittivity of the obtained polycrystalline BT 2 was higher than that of polycrystalline BT 2 in previous research [6][7][8] but much lower than that of single-crystalline BT 2 [11,12], which was caused by the random and disordered arrangement of b-axis oriented BT 2 in the sintered bodies. as is known to all, the needle-like BT 2 single crystal could be grown from a melt along the b-axis direction [12], which indicated that polycrystalline BT 2 with b-axis orientation could be obtained by a meltingsolidification method.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the dense and single-phased BT 2 sintered bodies with a preferred growth direction along the b-axis were obtained via a solid-state reaction of BaCo 3 with Tio 2 at 1025°C in air using B 2 o 3 as the additive [11]. The permittivity of the obtained polycrystalline BT 2 was higher than that of polycrystalline BT 2 in previous research [6][7][8] but much lower than that of single-crystalline BT 2 [11,12], which was caused by the random and disordered arrangement of b-axis oriented BT 2 in the sintered bodies. as is known to all, the needle-like BT 2 single crystal could be grown from a melt along the b-axis direction [12], which indicated that polycrystalline BT 2 with b-axis orientation could be obtained by a meltingsolidification method.…”
Section: Introductionmentioning
confidence: 99%
“…as is known to all, the needle-like BT 2 single crystal could be grown from a melt along the b-axis direction [12], which indicated that polycrystalline BT 2 with b-axis orientation could be obtained by a meltingsolidification method. According to this finding, Tu et al [7] had prepared b-axis oriented, single-phased and polycrystalline BT 2 by an arc melting process; however, a large amount of cracks were found in the obtained samples, which would affect the dielectric properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The single-crystalline BaTi 2 O 5 prepared by floating zone melting shows a high Curie temperature (T C = 430-475 ℃) and a high permittivity in b-direction without lead additives [19,20]. Hence, BaTi 2 O 5 ceramic is fabricated and studied as a promising environmentally friendly material [15,[21][22][23][24]. Polycrystalline BaTi 2 O 5 ceramic was prepared by laser rapid solidification method [22].…”
Section: Introductionmentioning
confidence: 99%
“…7) In practical applications, however, polycrystalline material is preferable to single crystalline material due to its ease of manufacturing and low cost. In a previous study, 8) we prepared (020) orientated polycrystalline BT 2 by arc melting. Substitution of foreign element has been commonly applied to improve and modify the performance of ferroelectric compounds.…”
Section: Introductionmentioning
confidence: 99%